Degradación de nutrientes y emisión de gases al fermentar ensilaje y heno de Calliandra calothyrsus y Vigna unguiculata en el sistema Rusitec - Bernal, L.; Ávila, P.; Ramírez, G.; Lascano Aguilar, Carlos Eduardo; Tiemann, Tassilo T.; Hess, H (2008)
The Rusitec System was used to evaluate apparent in vitro degradation of organic matter (OM), crude protein (CP), neutral and acid detergent fibers (NDF, ADF), and production of methane and ammonia in silage and hay of two legumes, tannin-containing, Calliandra calothyrsus and, non-tanniniferous, Vigna unguiculata, and mixtures of both legumes. There were eight experimental treatments, each replicated four times, in a randomized complete-blocks design. The four treatments based on silages were: T1, Calliandra 100%; T2, Vigna 100%; T3, Calliandra/Vigna 67/33%; T4, Vigna/Calliandra 67/33%; and in analogous fashion the four treatments based on hays, T5, T6, T7, and T8. Analysis of initial chemical composition showed lower CP content in the silage than in the hay of both legumes; higher NDF and ADF in silage than in hay of Calliandra, but the reverse situation in Vigna. Calliandra hay was much higher in tannin content than the silage. In OM and CP degradability, silages surpassed hays and Vigna surpassed Calliandra; production of CH4 and NH3 followed the same pattern. Degradabilities of NDF and ADF were lower in Calliandra and its 67% mixtures, for which even some negative values were obtained. The possible use of Calliandra in appropriate proportions to protect dietary proteins from ruminal degradation, thus becoming bypass protein, is suggested.